Investigating the impact of technology-supported 3E learning model in disaster education - Arıkan, Alaattin; Bilen, Mert; Aladağ, Elif (Springer Science and Business Media LLC, 2024)
AbstractThis research aimed to investigate the effect of a technology-supported 3E learning model on middle school students’ knowledge of disasters and their attitudes towards disaster preparedness. To this end, it used an explanatory sequential mixed methods design. Quantitative and qualitative data were used to describe how the technology-supported 3E learning model changes the learning environment. A pretest-posttest control group quasi-experimental design was used in the quantitative part of the research, and a case study was used in the qualitative part. The experimental procedure lasted for six weeks. The sample consisted of 33 fifth-grade students attending a public school. The Disaster Preparedness Attitude Scale, an achievement test, and an interview form were used as data collection tools. The analysis results showed that the experimental group achieved statistically significantly higher scores in the posttest and the retention test of the Disaster Preparedness Attitude Scale, and the achievement test compared to the control group. Additionally, according to student views, the technology-supported 3E learning model is more helpful in acquiring skills and values, provides the opportunity to learn by experiencing, increases students’ motivation, and facilitates effective disaster education. These results indicate that conducting activities on a subject that concerns the whole society, such as disasters, using advancing and innovative technological devices, preparing lesson plans, and demonstrating their effectiveness in education will make a significant contribution to the literature.
Keywords: 4. Education